Transforming pharmaceutical education: A needs-based global analysis for policy development - Alison Etukakpan; Nilhan Uzman; Ozge Ozer; Toyin Tofade; Silvana Nair Leite; Arinola Joda; Yahya Choonara; Chiluba Mwila; Lilian M. Azzopardi; Aukje K. Mantel-Teeuwisse; Mohammad Rahal; Rula Darwish; et al. (Elsevier, 2023)
Background: A needs-based approach is desirable for the transformation of pharmaceutical education, and to link pharmaceutical education with the health needs of populations and national priorities. There are varying levels of data in the literature on the status of pharmaceutical education in all six World Health Organization (WHO) regions, especially in the context of needs identification and evidence-based policy interventions. The framework for this study was the FIP Development Goals. Objectives: The aim of the study was to develop evidence-based policies through a needs-based approach for pharmaceutical education transformation nationally, regionally and globally by addressing the following objectives: 1. Identify global and regional needs in pharmaceutical education, through a regional SWOT analysis and prioritization of FIP development goals; 2. Develop valid and credible regional roadmaps for pharmaceutical education advancement according to the identified prioritized goals and 3. Develop a global call to action as a policy intervention for advancing pharmaceutical education. Methods: This study was conducted between 2020 and 2021 using a mixed methods approach. Surveys of higher education institutions and a series of qualitative interviews were conducted with national professional leadership organizations, with further regional workshops having 284 participants recruited from the International Pharmaceutical Federation (FIP) membership base, spanning all six WHO regions. Results: Eleven out of 21 FIP DGs were identified as priorities for regional roadmaps and FIP DG 1 (Academic capacity) was identified as a priority in four regions. All regions had distinctive results with an area of commonality between them. There were common weaknesses in the adoption of competency-based education and inter-professional education. Conclusions: It is critical for every country and region to develop needs- and evidence-based policies for the transformation of pharmaceutical education, for which FIP DGs provide a systematic framework.